2018
DOI: 10.1186/s12885-018-3986-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment selection of early stage non-small cell lung cancer: the role of the patient in clinical decision making

Abstract: BackgroundThe objective of this study is to investigate the role and experience of early stage non-small cell lung cancer (NSCLC) patient in decision making process concerning treatment selection in the current clinical practice.MethodsStage I-II NSCLC patients (surgery 55 patients, SBRT 29 patients, median age 68) were included in this prospective study and completed a questionnaire that explored: (1) perceived patient knowledge of the advantages and disadvantages of the treatment options, (2) experience with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 61 publications
3
33
0
Order By: Relevance
“…The third is that as patients live beyond their original prognosis, they are able to turn their attention to other health concerns, and there is limited research and standardized practices around treatment for health issues concomitant to stage IV NSCLC. Recent research finds that a significant percentage of patients treated for NSCLC experience decisional conflict around their therapy and feel uninformed [68]. While our research corroborates findings of patients feeling uniformed and conflicted, we observed patients to experience significant emotional strain as they continued living in limbo while seeking information on their health and treatment.…”
Section: Discussionsupporting
confidence: 83%
“…The third is that as patients live beyond their original prognosis, they are able to turn their attention to other health concerns, and there is limited research and standardized practices around treatment for health issues concomitant to stage IV NSCLC. Recent research finds that a significant percentage of patients treated for NSCLC experience decisional conflict around their therapy and feel uninformed [68]. While our research corroborates findings of patients feeling uniformed and conflicted, we observed patients to experience significant emotional strain as they continued living in limbo while seeking information on their health and treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, most patients reported having several discussions about treatment options with their physician before a decision was made, and the physician’s recommendation and the information provided in those discussions may be highly influential on the patient’s decision. The importance of physician interactions in treatment decision-making was also recently shown for early-stage NSCLC patients when deciding about surgery and radiotherapy [ 19 ]. In a cross-sectional survey conducted after a decision was made, but before treatment, 85% of patients indicated that decision-making should ideally be shared between the patient and physician.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, physicians reported using MT among patient populations not included in NCCN guidelines for MT at the time of the survey. A recent survey of oncologists in the USA also reported that oncologists recommended lung cancer treatments outside of current recommended treatment strategies; approximately half of surveyed oncologists indicated that they would recommend chemotherapy for patients with advanced lung cancer with an ECOG PS of 3 (with no pain) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, decisional conflict is expected to occur also in the surgical field [6]. However, the research targeted decision at surgery has been rarely performed.…”
Section: Introductionmentioning
confidence: 99%